Implementing a general practitioner-to-general physician eConsult service (eConsultant) in Australia - Jennifer Job; Caroline Nicholson; Zoe Calleja; Claire Jackson; Maria Donald (BMC, 2022)
Abstract Background In response to lengthy wait times for specialist outpatient appointments, electronic consultation (eConsult) services have developed globally, providing asynchronous, secure and timely communication between general practitioner (GP) and specialist. This study aims to track adoption of a Queensland eConsultant service in two Australian Primary Health Networks (Western Queensland and Brisbane South) to understand key barriers and enablers to adoption and inform modification of the implementation strategy.  Methods Our theory-informed mixed-methods evaluation assessed implementation between July 2020 and March 2022. Adoption and implementation activities were prospectively recorded in bespoke tracking spreadsheets with implementation activities coded against the Expert Recommendations for Implementing Change (ERIC) strategies. Semi-structured interviews with GPs and stakeholders informed by the Consolidated Framework for Implementation Research (CFIR) were conducted to understand determinants of implementation.  Results Of the 40 practices invited to take part in the eConsultant service, 20 (50%) enrolled. Of the 97 GPs who consented, 38 sent at least one Request for Advice (RFA) to the eConsultant with a total of 112 RFA sent. Implementation was predominantly guided by eight strategies. Qualitative interviews were conducted with 11 GPs and 4 stakeholders (12 from rural/remote regions, 11 females and two sole practitioners). Interviewees felt the eConsultant service supported outpatient appointment avoidance and provided efficient, timely access to specialist support for GPs and their patients. Barriers identified to using eConsultant related to digital infrastructure, competing priorities, and keeping the service 'front of mind'. Key enablers identified were the relative advantage of eConsultant over other options, patient benefits and COVD-19 facilitating the use of digital technology. Conclusions This evaluation highlighted service enablers as well as user priorities for broader implementation. A focus on a well-integrated digital system and availability of a variety of eConsultant specialties are seen as key strategies to embedding the eConsultant option in GP advice processes in Australia.